PRADOC: a trial on the efficiency of a transition care management plan for hospitalized patients with heart failure in France. (25th December 2020) - Duflos, Claire; Labarre, Jean‐Philippe; Ologeanu, Roxana; Robin, Marie; Cayla, Guillaume; Galinier, Michel; Georger, Frédéric; Petroni, Thibaut; Alarcon, Clément; Aguilhon, Sylvain; Delonca, Christine; Battistella, Pascal; et al.
Abstract: Aims: Transition care programmes are designed to improve coordination of care between hospital and home. For heart failure patients, meta‐analyses show a high efficacy but with moderate evidence level. Moreover, difficulties for implementation of such programmes limit their extrapolation. Methods and results: We designed a mixed‐method study to assess the implementation of the PRADO‐IC, a nationwide transition programme that aims to be offered to every patient with heart failure in France. This programme consists essentially in an administrative assistance to schedule follow‐up visits and in a nurse follow‐up during 2 to 6 months and aims to reduce the annual heart failure readmission rate by 30%. This study assessed three quantitative aims: the cost to avoid a readmission for heart failure within 1 year (primary aim, intended sample size 404 patients), clinical care pathways, and system economic outcomes; and two qualitative aims: perceived problems and benefits of the PRADO‐IC. All analyses will be gathered at the end of study for a joint interpretation. Strengths of this study design are the randomized controlled design, the population included in six centres with low motivation bias, the primary efficiency analysis, the secondary efficacy analyses on care pathway and clinical outcomes, and the joint qualitative analysis. Limits are the heterogeneity of centres and of intervention in a control group and parallel development of other new therapeutic interventions in this field. Conclusions: The results of this study may help decision‐makers to support an administratively managed transition programme.